Comparison between Caprini and Padua risk assessment models for hospitalized medical patients at risk for venous thromboembolism: a retrospective study - Liu, Xiaohan; Liu, Chengyuan; Chen, Xi; Wu, Wenwen; Lu, Gendi (Interactive cardiovascular and thoracic surgery, 2016)
OBJECTIVES This study aimed to evaluate the validity of the risk assessment model (RAM) of Caprini and Padua in identifying venous thromboembolism (VTE) among hospitalized medical patients. METHODS This retrospective study reviewed a total of 320 VTE and 320 non-VTE patients. Baseline demographics and clinical data of these patients were all recorded. The Caprini and Padua RAMs were implemented and the individual scores of each risk factor were summed to generate a cumulative risk score. Meanwhile, the sensitivity, specificity, and positive and negative predictive values of these two models were analysed. Receiver operating characteristic (ROC) curve was plotted to calculate the area under the curve (AUC) and the Youden index. RESULTS Significant differences were observed in risk factors between VTE and non-VTE patients. More VTE patients were classified into the high–superhigh risk level by the Caprini RAM than the Padua RAM (70.9 vs 23.4%, P < 0.01). The sensitivity and positive and negative predictive values in the Caprini RAM were higher than those in the Padua RAM (P < 0.05). However, the specificity of the Caprini RAM was lower than that of the Padua RAM (P < 0.01). The AUC and the Youden index were higher in the Caprini RAM than in the Padua RAM (P < 0.01), whereas the Youden index in the Padua RAM at critical point 4 was lower than that at critical point 3 (0.010 vs 0.140, P < 0.05). CONCLUSIONS The Caprini RAM was suggested to be more effective than the Padua RAM for identification of hospitalized medical patients at risk for VTE.